Surgical Management of Refractory Pulmonary Actinomycosis: A Case Report - Mauricio Alejandro Saldaña-Ruiz; Jaime Eugenio Espinosa-Mora; Mauricio Linnery Rendón-Saldívar; Federico Ortiz-Alonso; Leopoldo David Trujillo-García (International Journal of Medical Students, 2025)
Background: Pulmonary actinomycosis is an uncommon disease with a non-specific clinical presentation, challenging and usually leads to a misinterpretation of malignancy rather than infection.